Effects of Helicobacter pyloriinfection on gastric acid secretion and serum gastrin levels in Mongolian gerbils. Issue 6 (1st June 2001) - Takashima, M; Furuta, T; Hanai, H; Sugimura, H; Kaneko, E
Abstract : BACKGROUND AND AIMS: Body gastritis caused by Helicobacter pylori infection appears to inhibit gastric acid secretion. The aim of this study was to determine the effects of H pylori infection on gastric acid secretion and clarify its mechanisms with reference to interleukin 1β (IL-1β). METHODS: (1) Mongolian gerbils were inoculated orally with H pylori . Before, six, and 12 weeks after inoculation, serum gastrin levels, gastric acid output, and IL-1β mRNA levels in the gastric mucosa were determined. Pathological changes were also determined according to the updated Sydney system. (2) Effects of recombinant human IL-1 receptor antagonist (rhIL-1ra) on gastric acid output and serum gastrin levels were also determined. RESULTS: (1) Scores for activity and inflammation of gastritis and serum gastrin levels were significantly increased, and gastric acid output was significantly decreased six and 12 weeks after inoculation with H pylori. IL-1β mRNA levels in the gastric mucosa were also elevated six and 12 weeks after inoculation with H pylori . (2) Acid output and serum gastrin levels in the infected groups returned to control levels after rhIL-1ra injection. CONCLUSIONS: Gastric acid secretion is decreased and serum gastrin levels are increased in Mongolian gerbils infected with H pylori . This change in gastric acid secretion appears to be mediated by IL-1β induced by H pylori infection.